Physical therapy of gastrointestinal non-motor manifestations of Parkinson's disease according to coprological methods of nutrition assessment - Labinsky, Andriy (Journal of Education, Health and Sport, 2017)
Topicality. Determination of the level of efficiency of using physical therapy with nutritional correction of nutrition in gastrointestinal non-motor manifestations of Parkinson's disease. Objectives of the study: to analyze and systematize modern scientific and methodological knowledge and results of practical experience of domestic and foreign researchers on the use of physical therapy with nutritional correction of nutrition in gastrointestinal non-motor manifestations of Parkinson's disease - to study and evaluate the status of patients by nutritional methods non-motor manifestations of Parkinson's disease. Research results. The results of the examination of patients and their nutritional status revealed a significant improvement in the condition of patients after the course of physical therapy with the appointment of a special diet for biorhythms with the onset of persistent hunger. The results were confirmed by scopological studies, during which they found a significant reduction in the number of undigested substances in the stool microscopy of patients after a course of physical therapy against the background of nutritional correction. Conclusions. The analysis of the obtained results shows that physical therapy against the background of nutritional correction improves the condition of patients with gastrointestinal non-motor manifestations of Parkinson's disease according to the data of coprological study. The developed program of physical therapy against the background of a special diet is effective for the correction of gastrointestinal non-motor manifestations of Parkinson's disease and may be recommended for wider introduction.